An exceptional P-H phosphonite: Biphenyl-2,2'-bisfenchylchlorophosphite and derived ligands (BIFOPs) in enantioselective copper-catalyzed 1,4-additions - Kop-Weiershausen, T.; Lex, J.; Neudörfl, J.-M.; Goldfuss, B. (Beilstein Journal of Organic Chemistry, 2005)
Biphenyl-2,2'-bisfenchol (BIFOL) based chlorophosphite, BIFOP-Cl, exhibits surprisingly high stabilities against hydrolysis as well as hydridic and organometallic nucleophiles. Chloride substitution in BIFOP-Cl proceeds only under drastic conditions. New enantiopure, sterically demanding phosphorus ligands such as a phosphoramidite, a phosphite and a P-H phosphonite (BIFOP-H) are hereby accessible. In enantioselective Cu-catalyzed 1,4-additions of ZnEt2 to 2-cyclohexen-1-one, this P-H phosphonite (yielding 65% ee) exceeds even the corresponding phosphite and phosphoramidite.
Keywords: phosphorus ligands; chirality; biaryls; asymmetric conjugate additions; phosphoramidites; phosphites; phosphonites; X-ray analyses